Consistency and fusion of suppositories: Test methods - Suñé, José María; Ruiz, María Josefa (Ars Pharmaceutica (Internet), 1964)
The pharmaceutical form of the suppository has reached an extraordinary diffusion in the last quarter of the century, becoming the third in importance.For the pharmacist and in a special way in the Speciality Laboratory, it has involved the introduction of new liposoluble excipients substitute for cocoa butter and hydrosoluble substitutes of the classic glycerogelatine and the sodium glycerin-stearate mixture.